Analysis of the attack tempo determinants in volleyball's complex II - a study on elite male teams - Castro, J. M.; Mesquita, I. (International Journal of Performance Analysis in Sport, 2010)
This study aims to analyse possible determinants that might predict the attack tempo in the Volleyball's complex II. A total of 881 actions were analyzed from 28 games of the national male teams presented in the World Cup 2007. A multinomial logistic regression was applied, with the level of significance determined in a=0.05. The variables dig type, dig efficacy and setting zone demonstrated predictive power of the attack tempo. The dig without all attack options and the dig with fall decreased the probability of quicker attack tempos. The higher frequency of the dig without all attack options is, perhaps, an explanation to the high values of the non acceptable setting zone, whose occurrence promotes a slower attack organization. In this sense, the increasing of the dig efficacy and stabilization of the dig type will improve the dig action to acceptable and excellent setting zones, which will increase the use of quicker attack tempos.